Prescribing patterns of statins and associated factors among type 2 diabetes mellitus patients attended at Jugol General Hospital in eastern Ethiopia: A cross-sectional study - Nigussie, Shambel; Demeke, Fekade (Frontiers in Clinical Diabetes and Healthcare, 2023)
Background: Though most clinical practice guidelines support the use of statins in type 2 diabetes mellitus patients to lower the risk of cardiovascular disease, nothing is known about prescribing patterns of statins in Jugol General Hospital, Eastern Ethiopia. Objective: This study aimed to assess the prescribing patterns of statins and associated factors among type 2 diabetes mellitus patients attended in Jugol General Hospital, Eastern Ethiopia. Methods: A retrospective cross-sectional study was conducted among 423 type 2 diabetes mellitus patients who had been under follow-up from June 1, 2017, to June 1, 2022. The study participants were enrolled consecutively using convenience sampling technique. The data were extracted from medical records using the data abstraction checklist. Using a data abstraction checklist, data were extracted from medical records. The extracted data were entered into Epi data version 3.1 and exported to SPSS version 22 for analyses. The presence and strength of statistically significant association was measured using p < 0.05 and Adjusted Odds Ratio with its 95% confidence intervals. Result: The medical records of 423 patients were reviewed. In the review, 410 of these patients' medical records had complete information and were entered for analysis. Majority of the study participants were females (72.2%) and between the age of 40 - 65 years (61.2%). All of the study participants were eligible for statin prescription; however, statins were prescribed only for 257 (62.7%) study participants. Of statins prescribed, moderate-dose intensity statins were prescribed for 40 (15.6%) participants who were in high risk . Atorvastatin was the most commonly (93.3%) prescribed statin. Presence of hypertension, coronary artery disease, and cerebrovascular event were significantly associated with statin prescribing. Conclusion: The magnitude of prescribing statins for type 2 diabetes mellitus patients was low in comparison to the clinical practice guidelines recommendation. This finding is an alarming and a call for action to improve the execution of clinical practice guidelines for the benefit of this high-risk population.